2012
DOI: 10.1007/s00264-012-1556-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonunion of fibula: a systematic review

Abstract: Purpose The purpose of this systematic review was to analyse the available evidence regarding nonunions of the fibula. We focussed on the incidence, risk factors, evaluation, and treatment modalities for fibular nonunions as evident in the current literature and propose a treatment algorithm. Methods This was an Institutional Review Board (IRB) exempt study performed at a level one trauma centre. We systematically reviewed the published evidence on fibular nonunion or delayed union from 1950 to February, 2011.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Factors that can increase the risk of non-union include increased age, obesity and history of smoking, none of which apply to our patient [2][3][4]11]. The patient is young, active and healthy with no history of substance or tobacco use.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Factors that can increase the risk of non-union include increased age, obesity and history of smoking, none of which apply to our patient [2][3][4]11]. The patient is young, active and healthy with no history of substance or tobacco use.…”
Section: Discussionmentioning
confidence: 99%
“…However, non-unions do occur and several ways have been documented on how to treat them [3]. In a systematic review of fibula non-unions, Bhadra et al [3] reviewed the treatment options found in the literature [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations